(untitled) (Journal of Laboratory Animal Science, 2019)
Sub chronic toxicity study of mixed culture filtrate of Rhizopus oryzae, Fusarium verticilloides and Fusarium xylarioides isolated from the fungal contaminated ground nut hay was conducted in rats. The fungi were isolated from the contaminated groundnut hay which caused mycotoxicosis in cross bred cattle, exhibited the clinical signs of colic, tenesmus, ruminal atony, anorexia, bleeding from nostrils, rectum and fly bite site. The rats were gavaged with culture filtrate at the dose level of 0.5, 1 and 2 ml daily for 90 days. Clinical signs observed were diarrhea, weakness, severe arching of back, swollen forehead and conjunctival hemorrhage. Cutaneous hemorrhagic patches on back, scrotum, abdomen, ears and legs region seen. There was a significant increase (P <0.05) in serum concentrations of creatinine, urea nitrogen, ALT and AST indicated the renal and hepatic damage which was confirmed by histopathology. There were lesions in brain and GI tract of the treated rats. The present study indicated the toxic feature of the mixed culture filtrates of fungi Rhizopus oryzae, Fusarium verticilloides and Fusarium xylarioides isolated from ground nut hay.